Pengaruh Komunikasi Interpersonal Terhadap Citra Perusahaan dan Kinerja Keuangan Studi Kasus PT. Bank Pembiayaan Rakyat Syariah (BPRS) - Fikrotul Ulyah; Ririn Susilawati (STAIFAS-Press, 2017)
ABSTRACT Good communication can attract new customer so companies can earn profits that have an impact on financial performance.The purpose of this study is to analyze the influence of interpersonal communication on crporate image and the financial performance study of PT. BPRS Lantabur Tebuireng Jombang. The population in this research is the entire clientele of PT. BPRS Lantabur Tebuireng Jombang is 980 customer and sample as much as 98 client using random sampling techniques. It also uses financial report publication company from 2011 to 2016. These studies use quantitative methods using simple regression analysis of data with 5% significance.The results of the analysis show that variable interpersonal communication significantly influential taking action against corporate image with t value calculate of 8.06 and have 0,00 significance. Whereas interpersonal communication variables there is not influance against financial performance because the t value calculate amounted to 1.236 with 0.236 significanc Keywords: Corporate Image, BPRS Lantabur, Financial Performance Interpersonal Communication.